PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK (Studi Empiris Pada Perusahaan Non-Keuangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2013) - Novriansyah Zulkarnaen (Faculty of Economic and Business, 2015)
This research aims to analyze and obtain empirical evidence about the effect of independent commissioner, compensation of management executives and institusional investor to tax management. The independent variabels used are independent commissioner, compensation of management executives and institusional investor. The dependent variabel used is tax management. The research population was companies listed in Indonesia Stock Exchange (IDX) in period of 2010-2013. Sample was collected by purposive sampling method. Total 86 companies were taken as study’s sample. Analysis method of this research used multiple regression. The result shows independent commissioner, compensation of management executives and institusional investor partially influence to tax management with significant value as 0,004, 0,046 and 0,000. Then, independent commissioner, compensation of management executives and institusional investor simultaneously and significantly influence to tax management, It can be seen from the significance value of 0,000.DOI: 10.15408/ess.v5i1.2335